CIN85/RukL is a novel binding partner of nephrin and podocin and mediates slit diaphragm turnover in podocytes - Tossidou, Irini; Teng, Beina; Drobot, Lyudmyla; Meyer-Schwesinger, Catherine; Worthmann, Kirstin; Haller, Hermann; Schiffer, Mario (Journal of Biological Chemistry, 2010)
Podocyte damage is the basis of many glomerular diseases with ultrastructural changes and decreased expression of components of the slit diaphragm such as nephrin and podocin. Under physiological conditions it is likely that the slit diaphragm underlies permanent renewal processes to indemnify its stability in response to changes in filtration pressure. This would require constant reorganization of the podocyte foot process and the renewal of slit diaphragm components. Thus far, the mechanisms underlying the turnover of slit diaphragm proteins are largely unknown. In this manuscript we examined a mechanism of nephrin endocytosis via CIN85/RukL-mediated ubiquitination. We can demonstrate that the loss of nephrin expression and onset of the proteinuria in CD2AP-/- mice correlates with an increased accumulation of ubiquitinated proteins and expression of CIN85/RukL in podocytes. In cultured murine podocytes CD2AP deficiency leads to an early ubiquitination of nephrin and podocin after stimulation with fibroblast growth factor-4. Binding assays with different CIN85/Ruk isoforms and mutants showed that nephrin and podocin are binding to the coiled-coil domain of CIN85/Ruk L. We found that in the presence of CIN85/RukL, which is involved in down-regulation of receptor-tyrosine kinases, nephrin is internalized after stimulation with fibroblast growth factor-4. Interestingly, coexpression of CIN85/RukL with CD2AP led to a decreased binding of CIN85/RukL to nephrin and podocin, which indicates a functional competition between CD2AP and CIN85/RukL. Our results support a novel role for CIN85/RukL in slit diaphragm turnover and proteinuria. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2020-11-12